Employees’ perception towards the implementation of corporate governance principles: A Malaysia perspective - Kumutha, Mani (2023)
“Corporate governance” is basically a kind of process, through which the management of the organizations or companies is successfully able to implement as well as enact the “best management practices”. Corporate governance (CG) refers to the system of rules, practices, and processes by which a company is directed and controlled. It involves balancing the interests of a company's many stakeholders, such as shareholders, management, customers, suppliers, financiers, government, and the community. This research aims to find the employees’ perception towards the implementation of corporate governance principles: a Malaysia perspective. The population of the study consists of employees from the manufacturing industry from Shah Alam. The total sample selected for the research are 357 respondents. The research instrument used was a questionnaire using a Likert scale and the results were analyzed through the Statistical Package for the Social Sciences (SPSS) to measure whether there is a significant relationship between the study variables. The result shows that commitment has a significant relationship with the employee perception towards corporate governance. Next, the result also shows that there is a significant relationship between employee perception towards corporate governance. Besides, research findings show that there is a significant relationship between employee perception towards corporate governance. Besides, the study also found that there is a significant relationship between employee perception towards corporate governance. Organizations should prioritize demonstrating a strong commitment to ethical principles, transparency, and accountability to create a positive perception among employees. The manager can build commitment among employees by fostering a positive and inclusive work environment where employees feel valued, empowered, and recognized for their contributions. Future researchers can enhance the research towards more employees outside the actual field. By broadening the scope to include employees from various departments, a more comprehensive understanding of the organization's dynamics could be achieved.